Mojokerto Marketplace Determinants of Product Reviews, Convenience, Trust, and Price on Purchase Decisions on Shoppe - Elly Joenarni; Mokhammad Ridha; Devi Iriandha Widyastuti; Eny Rachmawati; Adil Abdillah (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The goal of this study is to discover how the Shopee Mojokerto market's consumers make purchasing decisions in relation to product ratings, convenience, trust, and pricing. Design/methodology/approach: A good illustration of quantitative research is this. A purposive sampling technique was used to interview 100 respondents for this study's sample. The data analysis approach employs multiple linear regression analysis, t-tests, and F-tests. SPSS 21 is used to do the computations. Findings: The test results reveal that in the Shopee market in Mojokerto, convenience, trust, and price have a favorable and considerable influence on purchasing decisions, but product dimensions have minimal effect. The primary factor influencing Mojokerto Shopee purchases is easy. Paper type: Research paper